IDENTIFIKASI PETANI KELAPA DI KELURAHAN BEO TIMUR KECAMATAN BEO KABUPATEN KEPULAUAN TALAUD - Rompah, Joseph Lorens; Manginsela, Elsje Pauline; Baroleh, Jenny (AGRI-SOSIOEKONOMI, 2022)
The purpose of this study was to identify the characteristics of coconut farmers in Beo Timur Sub district, Beo District, Talaud Regency. The research was conducted from November 2021 to January 2022, The data used in this study are primary data and secondary data and then analyzed descriptively. The results showed that the coconut farmers in Beo Timur Sub District had an average age of 47 years (81.48 percent). Most coconut farmers have an education level of highscool and Bachelor's as many as 11 people or 40.74 percent. With 5 years of farming experience (59 percent). Coconut farmers have other jobs, namely as fishermen, carpenters and coolies (48 percent), civil servants, shop entrepreneurs, credit counters, motorcycle taxis. Coconut plantations are mostly planted with other crops, namely cloves and nutmeg (67 percent). Some coconut farmers plant rambutan and durian trees as well as seasonal crops such as cassava and chilies.